2008
DOI: 10.1007/s00268-008-9582-0
|View full text |Cite
|
Sign up to set email alerts
|

Choledochal Cysts in Children: Epidemiology and Outcomes

Abstract: The epidemiology of choledochal cysts in Thai children was similar to cases reported from other regions. Early diagnosis and treatment, particularly in children under 2 years of age, should be emphasized, because these patients are at a higher risk for development of chronic liver disease and poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
3
18
0
Order By: Relevance
“…Additionally, Mishra et al [15] observed a prevalence of cyst type IC in the infant group and of type IF in the older group; whether this difference in cyst type I prevalence derives from the fact that their subjects resided in India rather than Taiwan is unclear. In agreement with the present report, Singhavejsakul and Ukarapol [21] reported that cyst type I was most common among children in Thailand, followed by cyst type IV.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, Mishra et al [15] observed a prevalence of cyst type IC in the infant group and of type IF in the older group; whether this difference in cyst type I prevalence derives from the fact that their subjects resided in India rather than Taiwan is unclear. In agreement with the present report, Singhavejsakul and Ukarapol [21] reported that cyst type I was most common among children in Thailand, followed by cyst type IV.…”
Section: Discussionsupporting
confidence: 93%
“…For example, children tend to present with such features as abdominal pain, jaundice, and abdominal mass whereas adults present more often with common biliary or infectious complications and tend to develop choledocholithiasis, malignant transformation, and perioperative and long-term complications more frequently [3,10,15,17,21]. Additionally, the clinical and operative findings for neonates/ infants with choledochal cysts differ from those for the classical pediatric group or for adults with these cysts.…”
Section: Introductionmentioning
confidence: 82%
“…Choledochal cyst has been considered as disease of childhood and most patients present during first decade of life [1,3]. In our experience, 50 % of the patients were adults.…”
Section: Discussionmentioning
confidence: 95%
“…Traditionally, there are five varieties of CDCs that are classified according to their location in the biliary tree by the Todani modification of the Alonso-Lej classification [2]. Classically, this disease has been described to have a higher incidence of diagnosis during the first decade of life as well as a predominance in females of 3-4:1 [35]. Additionally, there is a much higher prevalence of CDCs in southeast Asian countries, with an overall incidence of 1:1000 compared with 1:100 000–150 000 in Western countries.…”
Section: Introductionmentioning
confidence: 99%